Eight new Brazilian species of Fonsecaiulus (Hemiptera: Cicadellidae: Cicadellini), new records of species, and key to males of the genus - Felix, Márcio; Mejdalani, Gabriel; Domahovski, Alexandre C.; Cavichioli, Rodney R. (Zootaxa, 2022)
Eight new Brazilian species of the South American sharpshooter genus Fonsecaiulus Young, 1977 are described and illustrated. Three new species are from Minas Gerais State (F. youngi sp. nov., F. spinosus sp. nov., and F. unciformis sp. nov.), two from Paraná State (F. chelatus sp. nov. and F. takiyae sp. nov.), one from Paraná and Rio Grande do Sul states (F. truncatus sp. nov.), one from Maranhão State (F. longiramus sp. nov.), and one is recorded only from “Brazil” (F. alvarengai sp. nov.). The species descriptions are focused on the male and female terminalia. With the addition of these new taxa, Fonsecaiulus now comprises 17 species; a dichotomic key to males of all these species is provided. New distribution records are given for the following species: F. cognatus (Schmidt, 1928)—Paraná State, F. rectangularis Felix et al., 2015—Bahia State, and F. sanguineovittata (Signoret, 1855)—Paraguay, Canindeyú Department. Notes on the morphology and distribution of the genus are added.